2022
DOI: 10.7150/jca.66850
|View full text |Cite
|
Sign up to set email alerts
|

LINC00630 promotes cholangiocarcinoma cell proliferation, migration and invasion by mediating the miR-199a/FGF7 axis

Abstract: Cholangiocarcinoma (CCA) is a type of cancer with a relatively low morbidity, but poor prognosis. Aberrant long non-coding RNA (lncRNA) expression has been observed in the pathological development of CCA. In the present study, lncRNA long intergenic non-protein coding RNA 630 (LINC00630) was found to be significantly upregulated in CCA tissues and cultured cells. LINC00630 expression was positively associated with histological differentiation, TNM stage and lymph node invasion. Short hairpin RNA (sh)-LINC00630… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…LncRNAs play a critical role in the pathological development of various diseases, including malignant tumors [ 39 ]. It has been demonstrated that lncRNA LINC00630 can effectively inhibit the proliferation, migration, and invasion of cholangiocarcinoma cells by mediating the miR-199a/FGF7 axis [ 40 ]. LncRNA HOX transcript antisense RNA has been reported to play an important role in the progression of osteoarthritis, and it enhances mechanical stimulation-induced chondrocyte apoptosis by mediating the miR-221/BBC3 axis in C28/I2 cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs play a critical role in the pathological development of various diseases, including malignant tumors [ 39 ]. It has been demonstrated that lncRNA LINC00630 can effectively inhibit the proliferation, migration, and invasion of cholangiocarcinoma cells by mediating the miR-199a/FGF7 axis [ 40 ]. LncRNA HOX transcript antisense RNA has been reported to play an important role in the progression of osteoarthritis, and it enhances mechanical stimulation-induced chondrocyte apoptosis by mediating the miR-221/BBC3 axis in C28/I2 cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%